Exosomes derived from syncytia induced by SARS-2-S promote the proliferation and metastasis of hepatocellular carcinoma cells - Huilong Li; Huilong Li; Haotian Lin; Haotian Lin; Tinghui Fan; Linfei Huang; Li Zhou; Xiaoyu Tian; Ruzhou Zhao; Yanhong Zhang; Xiaopan Yang; Luming Wan; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionCoronavirus disease 2019 (COVID-19) is characterized by fever, fatigue, dry cough, dyspnea, mild pneumonia and acute lung injury (ALI), which can lead to acute respiratory distress syndrome (ARDS), and SARS-CoV-2 can accelerate tumor progression. However, the molecular mechanism for the increased mortality in cancer patients infected with COVID-19 is unclear.MethodsColony formation and wound healing assays were performed on Huh-7 cells cocultured with syncytia. Exosomes were purified from the cell supernatant and verified by nanoparticle tracking analysis (NTA), Western blot (WB) analysis and scanning electron microscopy (SEM). Differentially expressed proteins in syncytia-derived exosomes (Syn-Exos) and their functions was analyzed by Proteomic sequencing. Syn-Exo-mediated promotion of hepatocellular carcinoma cells was measured by CCK-8 and Transwell migration assays. The mechanism by which Syn-Exos promote tumor growth was analyzed by Western blotting. A patient-derived xenotransplantation (PDX) mouse model was constructed to evaluate the pathological role of the SARS-CoV-2 spike protein (SARS-2-S). The number of syncytia in the tumor tissue sections was determined by immunofluorescence analysis.ResultsSyncytium formation promoted the proliferation and migration of hepatocellular carcinoma cells. Proteomic sequencing revealed that proteins that regulate cell proliferation and metastasis in Syn-Exos were significantly upregulated. Syn-Exos promote the proliferation and migration of hepatocellular carcinoma cells. Animal experiments showed that a pseudotyped lentivirus bearing SARS-2-S (SARS-2-Spp) promoted tumor development in PDX mice. More syncytia were found in tumor tissue from SARS-2-Spp mice than from VSV-Gpp mice.ConclusionsSyn-Exos induced by SARS-2-S can promote the proliferation and metastasis of hepatocellular carcinoma cells.